"You Don't Mess With Black Twitter!": An Ubuntu Approach to Understanding "Militant" Twitter Discourse. Issue 3 (3rd July 2021) - Molefe, Motsamai; Ngcongo, Mthobeli
Abstract: The democratisation and proliferation of social media has seen the emergence of a distinct virtual community of Twitter users known as Black Twitter. This burgeoning community is characterised by discourses on cultural issues that are critical to the black community, such as race relations and identity politics in general. Black Twitter has often been criticised for its unashamed bashing of those who are perceived as displaying inauthenticity in their performance of identity and their positions on the critical issues debated on Twitter. This article reports on a study that employed a small-scale online ethnographic approach to collect a sample of tweets from a Twitter engagement with a South African public figure and media personality, the actress Nandi Madida. The article argues that through an African normative perspective known as ubuntu, the perceived harshness of South African Black Twitter users can be more usefully read as part of African cultural value of critical humanism. Ultimately, the traditional notion of ubuntu as simply friendliness towards a fellow human is challenged by broadening the concept to apply to notions that include seemingly violent forms of communication. This more robust view of ubuntu, whose application is demonstrated from the context of Black Twitter, ultimately seeks to make another person a better human even if it means public criticism.